Head shape disparity impacts pollutant accumulation in European eel. (September 2018) - De Meyer, Jens; Belpaire, Claude; Boeckx, Pascal; Bervoets, Lieven; Covaci, Adrian; Malarvannan, Govindan; De Kegel, Barbara; Adriaens, Dominique
Abstract: Several aspects of the life cycle of the critically endangered European eel ( Anguilla anguilla ) remain poorly understood. One such aspect is the broad-versus narrow-head dimorphism, and how this impacts their overall performance at different stages of their life cycle. At the yellow eel stage, the phenotypes show a trophic divergence. We investigated whether pollutant accumulation is affected by this disparity. We show that broad-headed eels contained higher concentrations of mercury and several lipophilic organic pollutants, compared to narrow-headed ones, irrespective of their fat content. The hereby confirmed link between the phenotypic disparity, its associated feeding ecology and its impact on pollutant accumulation thus raises further concerns about their migratory and reproductive success. Considering that pollution is an important contributor to the European eel's decline, our results demonstrate that broad-headed eels are more vulnerable to detrimental pollutant accumulation. This compromises their successful contribution to their population's reproduction and its restoration. Graphical abstract: Image 1 Highlights: In European eel populations, trophic segregation can govern pollutant uptake. Trophic segregation is associated with morphological specialization in head shape. Broad-headed morphs have a higher trophic position and accumulate more pollutants. The uptake rate of biomagnifying pollutants is determined by their lipophilicity. Broad-headed morphs also have less fat and thus possibly a lower reproductive success. Abstract : Pollutant uptake rate in European eel can be governed by trophic segregation associated with morphological specialization, with the rate depending on the contaminants lipophilicity.